Reflexiones, preguntas y sentires sobre la construcción y el ejercicio de pedagogías para la transformación: ¿cómo disputamos narrativas de dominicación a partir de epistemologías feministas? - nieto gómez, yuly andrea (Colombian Applied Linguistics Journal, 2023)
This article presents a reflection on the way feminist epistemology can become the basis of an EFL curriculum that challenges subordination and recognizes the power of embodied language as a starting point for critical openness and collective transformative action, based on theorizing my own experience as a feminist teacher. From two main arguments: 1. Language as a Site of Struggle: A Curriculum with Critical Empathy to Challenge Subordination and 2. Feminist Knowledge as Technology? Inquiring, weaving and imagining possible worlds from the classroom, I address how a feminist research perspective can foster a critical and creative view of material reality, by inviting students and teachers to interpret, reflect and take responsibility for the concrete dimension of the knowledge they are building; wondering how it is produced, under what conditions, for whom and the bodies producing it; feeling and recognizing oneself within the critique of these representations or matrixes of oppression trapped and guarded within our daily realities. In this reflection, I allow myself to invite teachers to promote a situated and critical teaching, where we feel autonomous to imagine class materials that challenge and unbalance these androcentric and essentialist academic structures of gender, race, class, nationality. Thus, the curriculum itself would be generating a sense of collective responsibility that allows claiming meanings outside of a dominant vision.